Circulating Tumor DNA-Based Detection of Microsatellite Instability and Response to Immunotherapy in Pancreatic Cancer - Kamatham, Saivaishnavi; Shahjehan, Faisal; Kasi, Pashtoon Murtaza (Frontiers in Pharmacology, 2020)
Pancreatic cancer is an aggressive malignancy with poor survival. Research has indicated the association of few genetic aberrations with pancreatic cancer. The data regarding the prevalence of microsatellite instability in pancreatic cancer is diverse and controversial. However, it could be an actionable target in pancreatic cancer especially due to availability of immune checkpoint inhibitors which has demonstrated promising results in different types of cancers. We present a case of pancreatic cancer whose microsatellite instability status was identified on liquid biopsy (circulating tumor DNA testing). Our patient showed a reasonable response to immunotherapy. We were able to do serial monitoring with liquid biopsy that showed clinical utility and validity.